Mortality prediction scores in burn patients – a comparative analysis: Burns Mortality prediction scores (Journal of Statistics on Health Decision, 2022)
Introduction:The aim of this study consisted of accuracy assessment and comparison of different mortality prediction models performance used in the burn population from our burns unit (BU), comparing survivors and non-survivors clinical and demographic characteristics. Methods:A retrospective study of adult burn patients admitted to our BU in a 5-year period was performed. Toxic epidermal necrolysis and polytraumatized patients were not included. Mortality rate was assessed. Survivors and non-survivors clinical and sociodemographic characteristics were analyzed and compared. Four models were included, namely Abbreviated Burn Severity Index (ABSI), Belgian Outcome in Burn Injury (BOBI), revised-Baux and Ryan model. Observed and predicted mortality were compared using Hosmer-Lemeshow test for models goodness-of-fit, receiver operating curves (ROC) and area under curve (AUC) for discriminative performance evaluation.Results:Our cohort consisted of 641 patients, in which 58,2% were male. Patients mean age was 60.02 ± 18.97 years and total burned surface area (TBSA) was 12.94 ± 15.11 %. Third degree burns were present in 71% and inhalation injury in 12.3%. Observed mortality rate was 9.4% (n=60). Non-survivors were significantly older (73 vs. 60 years; p